Academic adjustment of university students in relation to achievement motivation and self-efficacy - Elias, Habibah; Mahyuddin, Rahil; Noordin, Nooreen (2008)
Past studies show that more students leave colleges or universities without completing a degree. Hence it is critically important to understand the complex forces that influence successful academic adjustment during the first year (Tinto, 1993). A review of studies indicate that the higher the level of educational or occupational goals, the greater the probability the students will complete college education. Another important disposition is the students’ commitment to meet individual goals and the willingness to comply with the academic and social demands of the institution. Studies have also shown that students overcame the feelings of pressure and persisted in their education if they made a commitment to their educational goals and remain committed to the belief that attending their institution was the right decision (Sanders & Burton, 1996). Other factors found to be related to academic adjustment include self-confidence of intellectual ability, setting of high educational goals and self-esteem. Based on the above background, a study was conducted on 647 second year students in 4 universities in Klang Valley, Malaysia, to examine the level of their academic adjustment. The study also attempts to examine the relationship between two psychological factors namely achievement motivation and self-efficacy and academic adjustment. Results indicate that the majority (70.8%) of respondents are in the moderate level of academic adjustment, 15.8% in the low category and only 13.4 % in the high category. Positive and significant correlations were also found between academic adjustment and self-efficacy (r= .51, p<.01), achievement motivation (r= .42, p<.01) and CGPA(r=.12, p<.05). The implications are discussed in terms of teaching and learning in tertiary education.